PERAN PERBANKAN DALAM PENCEGAHAN PENDANAAN TERORISME - Erwin Asmadi (DE LEGA LATA: JURNAL ILMU HUKUM, 2016)
Funding is very essential as a forerunner to an act of terrorism because its propaganda product requires significant cost for the mobility, tools that are used as well as the ease-run actors to refrain from the pursuit of law. By this prevention, terrorism could be hampered by itself. Law Number 9 of 2013 concerning Prevention and Eradication of Crimes of Financing of Terrorism and other Laws give authority for banking to do prevention action for eradicating the terrorism mobility.